Rubus tianmuensis (Rosaceae), a new species from southeastern Anhui Province, China - Yin, Yongfei; Yi, Shanyong; Zhang, Ke (Phytotaxa, 2025)
Rubus tianmuensis, a newly discovered species belonging to the genus Rubus and Rosaceae family, is native to the Tianmu Mountains in southeastern Anhui Province. Genetically, it is related closely to R. chingii; however, several key morphological features position R. tianmuensis apart from R. chingii. Morphological analysis indicated that R. tianmuensis is characterized by persistently pedate leaves (vegetative and reproductive) with differentiated terminal leaflets on distinct petiolules, a trait consistently observed in both wild populations and cultivated specimens under under standard growth conditions. Additionally, the pedicels exhibit dense pubescence comprising short glandular trichomes and recurved prickles. Phylogenetic analysis based on ITS sequences confirmed the distinctiveness of this new species from R. chingii.